A Thermophile-Fermented Compost Modulates Intestinal Cations and the Expression of a Juvenile Hormone-Binding Protein Gene in the Female Larvae of Hercules Beetle Dynastes hercules (Coleoptera: Scarabaeidae) - Futo Asano; Taira Miyahara; Hirokuni Miyamoto; Hiroaki Kodama (Insects, 2023)
The Hercules beetle larvae grow by feeding on humus, and adding a thermophile-fermented compost to the humus can upregulate the growth of female larvae. In this study, the effects of compost on the intestinal environment, including pH, cation concentrations, and organic acid concentrations of intestinal fluids, were investigated, and the RNA profile of the fat body was determined. Although the total intestinal potassium ions were similar between the larvae grown without compost (control larvae) and those with compost (compost larvae), the proportion of potassium ions in the midgut of the compost larvae drastically increased. In the midgut, an unidentified organic acid was the most abundant, and its concentration increased in the compost larvae. Transcriptome analysis showed that a gene encoding hemolymph juvenile-binding protein (JHBP) was expressed in the compost female larvae and not in the control female larvae. Expression of many genes involved in the defensive system was decreased in the compost female larvae. These results suggest that the female-specific enhancement of larval growth by compost was associated with the increased JHBP expression under conditions in which the availability of nutrition from the humus was improved by an increase in potassium ions in the midgut.